A Brief Study on Benefits of Cloud Computing for Business Enterprises - Rajeyyagari, Sivaram; Malik, Chirag; Arora, Kapil; Reddy, B. Madhusudhan; Alahmari, Saad Ali; Marar, Sudheer S.; Chahal, Deepak (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Cloud computing has brought about a significant transformation in the way businesses function, presenting a wide array of advantages for enterprises regardless of their size. This technology, involving the storage and access of data and applications over the internet instead of on physical hardware, has become a fundamental element of contemporary business strategies. In this paper, we will delve into the various benefits that cloud computing offers to business enterprises.